Kajian Komunikasi Visual Heroisme dalam Film Animasi 2D The Battle of Surabaya - Dewi, Ni Putu Sinta; Fathoni, Muhammad (Jurnal Ilmu Sosial dan Humaniora, 2023)
Film is one of the communication media that is presented with audio visual and is able to influence the cognitive aspects of the audience. The Battle of Surabaya film is a form of 2D animated film, when examined in visual communication it contains messages of struggle and values ​​of heroism. This film tells about the battle that took place in the city of Surabaya on November 10, 1945. In the era of globalization, the attitude and spirit of heroism in the younger generation began to fade, so that through visual communication studies, the heroism of the film The Battle of Surabaya can be a reflection in building awareness for the next generation of the nation. The research method used in this research is descriptive qualitative research. The researcher performed Roland Barthes' semiotic data analysis technique through two levels of significance by explaining denotative and connotative meanings related to the study of visual communication in the 2D animated film The Battle of Surabaya. As for the findings in this study, the Battle of Surabaya, when examined in visual communication, heroism contains the meaning of the five principles of heroism. Referring to Roland Barthes's semiotics found related to sensitivity and concern for the motherland, sincerity to help others as shown by Yumna being a volunteer, love for the motherland which is shown visually with the national spirit in raising the red and white flag and lowering and tearing up the colonial flag. Sacrifices were made willingly to lose relatives, property and objects in order to defend the sovereignty of the Unitary State of the Republic of Indonesia. This patience and unity is visually demonstrated by the unity of the people of Surabaya in expelling the Dutch allies.